2021
DOI: 10.3390/genes12091342
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Identification of Homozygosity-Rich Genomic Regions in Seven Italian Heritage Turkey (Meleagris gallopavo) Breeds

Abstract: Italian autochthonous turkey breeds are an important reservoir of genetic biodiversity that should be maintained with an in vivo approach. The aim of this study, part of the TuBAvI national project on biodiversity, was to use run of homozygosity (ROH), together with others statistical approaches (e.g., Wright’s F-statistics, principal component analysis, ADMIXTURE analysis), to investigate the genomic diversity in several heritage turkey breeds. We performed a genome-wide characterization of ROH-rich regions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…We also identified candidate genes related to adaptation to hot temperatures in chicken species, such as FGF14 ( Coble et al, 2014 ) and NALCN ( Gu et al, 2020 ). The genes within the ROH island on GGA03 ( CLIC5, ENPP4, RCAN2, TDRD6, PLA2G7 IMP3, ANKRD66 MEP1A, ADGRF5 ) overlapped with an island reported in Italian turkey ( Bernini et al, 2021 ). Among these, we identified genes involved in immune responses, such as PLA2G7 ( Abasht et al, 2019 ) or reported as differentially expressed in dwarf and normal chickens ( ENPP4 ) ( Ye et al, 2014 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We also identified candidate genes related to adaptation to hot temperatures in chicken species, such as FGF14 ( Coble et al, 2014 ) and NALCN ( Gu et al, 2020 ). The genes within the ROH island on GGA03 ( CLIC5, ENPP4, RCAN2, TDRD6, PLA2G7 IMP3, ANKRD66 MEP1A, ADGRF5 ) overlapped with an island reported in Italian turkey ( Bernini et al, 2021 ). Among these, we identified genes involved in immune responses, such as PLA2G7 ( Abasht et al, 2019 ) or reported as differentially expressed in dwarf and normal chickens ( ENPP4 ) ( Ye et al, 2014 ).…”
Section: Discussionmentioning
confidence: 86%
“…We identified genes associated with adaptation and survival in hot conditions, such as TRMT1L ( Walugembe et al, 2019 ), TBC1D5 ( Fleming et al, 2017 ), and PTGS2 ( Zhao et al, 2022 ), as well as genes associated with immune ( KCNH8 ) ( He et al, 2015 ) and inflammatory response ( SATB1 ) ( Zhang et al, 2016 ). It is also interesting to note within the ROH island on GGA08 mapped candidate genes related to reproductive physiology in avian species ( PTGS2 and PLA2G4 ) ( Bernini et al, 2021 ), or associated with the regulation of growth and body size ( COL11A1 ) ( Wang et al, 2017 ) and feed intake efficiency ( AMY1A ) ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In chicken, several studies have reported that ROH regions can harbour candidate genes associated with production traits, immune response, and environmental adaptation [ 41 , 46 , 69 , 70 ]. For the group of heavy chickens, several genes in three regions of GGA3 have been reported as candidates related to muscle growth and overlap with ROH islands detected in Italian autochthonous turkey breeds [ 71 ]: BEND6 , which was identified as a candidate gene for intramuscular fat content in chicken [ 72 ]; COL21A1 , which is regulated by growth factors and is involved in muscle growth [ 73 ]; and BMP5 , which is a strong candidate gene for body size in livestock [ 74 ]. In the group of light chickens, we identified the AFF1 gene within a ROH island on GGA4, which is known to have a lower expression level in mallards (wild ancestors with a low weight) than in Pekin ducks (large body size), and thus is related with body weight [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“… Larkina et al (2021) proposed a phenotypic clustering model, supplementing the evolutionary model with two more breed types, i.e., dual purpose and fancy breeds (see breed examples in Table 1 ; Supplementary Material S2 ). Assessment of genetic diversity in various breeds is an important element in developing new strategies and applications for poultry breeding and production, as well as germplasm preservation ( Romanov and Weigend, 1999 ; 2001 ; Huang et al, 2016 ; Romanov et al, 2017 ; Romanov et al, 2021 ; Bernini et al, 2021 ; Dementieva et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%